2017
DOI: 10.4172/2576-1420.1000117
|View full text |Cite
|
Sign up to set email alerts
|

Association of Gene Polymorphisms and Serum Levels of IL-18 with the Susceptibility to Infection with Hepatitis B Virus

Abstract: Background: IL-18 gene polymorphisms is shown to be involved in various diseases. This study examines the influence of IL-18 gene polymorphism on the natural course of Hepatitis B Virus (HBV) infection together with the impact of serum levels in Iraqi population for the first time.Methods: A total of 55 patients and similar numbers of healthy controls were recruited in this study. Gene polymorphisms at positions -607C/A and -137G/C of IL-18 were examined using the allele-specific polymerase chain reaction (PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…When the association of the genotypes with HBV progression and subsequent HCC risk was studied, the IL-18 (-607) CA genotype was found to be a signi cant protective factor in Hepatitis B virus disease progression. This observation differed from the study conducted by Hasan et.al [40] who found no signi cant difference for CA genotype of IL-18(-607) in HBV infection. A study by Chang et al showed an association of the CA and CC genotypes of IL-18(− 607) with a signi cant decrease in the risk of renal cell carcinoma [RCC] compared with the AA genotype [41].…”
Section: Discussioncontrasting
confidence: 99%
“…When the association of the genotypes with HBV progression and subsequent HCC risk was studied, the IL-18 (-607) CA genotype was found to be a signi cant protective factor in Hepatitis B virus disease progression. This observation differed from the study conducted by Hasan et.al [40] who found no signi cant difference for CA genotype of IL-18(-607) in HBV infection. A study by Chang et al showed an association of the CA and CC genotypes of IL-18(− 607) with a signi cant decrease in the risk of renal cell carcinoma [RCC] compared with the AA genotype [41].…”
Section: Discussioncontrasting
confidence: 99%
“…The studied Chagas disease patient population presented a balanced gender composition, predominance of whites and a median age of 50 (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60) The entire study population was in Hardy-Weinberg equilibrium (HWE) (Supplementary Table 2). The genotype frequencies were also in HWE in whites and non-whites (Supplementary Table 2).…”
Section: Single Nucleotide Variant Genotype and Allele Distribution Imentioning
confidence: 99%
“…Variants of these two sites can not only affect IL18 transcription but also IFNg expression (58). The −607 A allele and AA genotype have been associated with lower IL18 transcriptional rate and/or protein levels than the C allele and CC genotype in different clinical and physiological settings (59)(60)(61)(62)(63), whereas the haplotype C-607/G-137 is associated with higher expression of IL18. Our analyses, however, did not identify a significant impact of IL18 −607 or IL18 −137 alleles/ genotypes on the T. cruzi parasitemic status.…”
Section: Hiv Infection Is Protective Against Development and Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…The -607 C-allele/CC-genotype carriage has been associated with higher levels of IL-18 in the serum and/or of mRNA expression (50,66,(68)(69)(70). In our study, we found higher Callele carriage on patients with the UC form of PCM (73.5%), whereas the AF and MC groups (with 46.2 and 51.1% of C-allele carriage, respectively) had already been reported to have higher serum IL-18 levels than those from the former group (19,20).…”
Section: Discussionmentioning
confidence: 99%